Citizens’ Perceptions on the Role of Court Sentencing in Crime Control: A Survey of Mthatha High Court Juridical Area in South Africa - Dlakulu, Anga; Mugari, Ishmael; Obioha, Emeka E. (International Journal of Criminology and Sociology, 2021)
For over a century, the role of court sentencing on crime deterrence has generated significant debate. In this study, we explored the citizens’ perceptions on the role of court sentencing in South Africa’s Mthatha area. The findings are looked in the context of the broad theories of punishment namely: retributive theory, deterrence theory, preventive theory, reformative theory and compensation theory. A total of purposefully sampled 90 respondents were invited to participate in this study through closed-ended questionnaires. The univariate perception results of the study reveal that reformation of the offender, protection of the offender from being harmed by the victim in retaliation, and ensuring that the victims get justice are the most significant roles of court sentencing. Collectively, the reality that severe sentence scares potential criminals not to commit crime stands out and is the most correlated role of court sentencing. Court sentencing was also viewed to be having two pronged preventive effect on criminal activities. First, the criminal is incapacitated from engaging in criminal activities during the time of imprisonment; and second, the offender is removed from the environmental factors that led to offending. As part of the conclusion, the study recommends sentencing policies that mainly support reformation of offenders.